Curcumin Inhibits Invasiveness and Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma Through Reducing Matrix Metalloproteinase 2, 9 and Modulating p53-E-Cadherin Pathway. (September 2015) - Lee, Alan Yueh-Luen; Fan, Chi-Chen; Chen, Yen-An; Cheng, Chieh-Wen; Sung, Ya-Ju; Hsu, Chih-Ping; Kao, Ting-Yu
Hypotheses . Epithelial-mesenchymal transition (EMT) and invasion play a critical role in cancer progression and metastasis. We have shown that low E-cadherin and high Twist expression are significantly correlated with prognostic survival prediction in oral squamous cell carcinoma (OSCC). This study aimed to determine the anti-invasive effect of curcumin on the expression of matrix metalloproteinases (MMPs) and of EMT regulators in OSCC. Methods . SCC-25 cells were treated with curcumin, and cell proliferation, invasion, and expression of MMPs and EMT regulators were assessed for cell viability by trypan blue exclusion, for invasion by Matrigel invasion chamber, and for EMT regulators and MMP changes in the levels of proteins by immunoblotting. Results . Our data showed that curcumin treatment not only decreased the expression of MMP-2 and MMP-9 to inhibit invasiveness in oral cancer but also modulated the expression of EMT markers, such as Snail, Twist, and E-cadherin, and induced p53 expression that is crucial to EMT repression. Conclusion . Curcumin has the potential to become an adjunctive regimen for the prevention of cancer progression and metastasis in oral cancer.